Mental health after first childbirth in women requesting a caesarean section; a retrospective register-based study - Louise Möller; Ann Josefsson; Marie Bladh; Caroline Lilliecreutz; Ellika Andolf; G. Sydsjö (BMC Pregnancy and Childbirth, 2017)
Abstract Background Psychiatric illness before delivery increases the risk of giving birth by caesarean section on maternal request (CSMR) but little is known about these women’s mental health after childbirth. In this study we aimed to compare the prevalence of psychiatric disorders five years before and after delivery in primiparae giving birth by CS on maternal request to all other primiparae giving birth, indifferent on their mode of delivery. Methods The study population comprised all women born in Sweden 1973–1983 giving birth for the first time in 2002–2004. Psychiatric diagnoses, in- and outpatient care were retrieved from the National Patient Register in Sweden. The risk of psychiatric care after childbirth was estimated using CSMR, previous mental health and sociodemographic variables as covariates. Results Psychiatric disorders after childbirth were more common in women giving birth by CSMR compared to the other women (11.2% vs 5.5%, p < 0.001). CSMR increased the risk of psychiatric disorders after childbirth (aOR 1.5, 95% CI 1.2–1.9). The prevalence of psychiatric disorders had increased after compared to before childbirth (mean difference 0.02 ± 0.25, 95% CI 0.018–0.022, p < 0.001). Women giving birth by CSMR tended to be diagnosed in the inpatient care more often (54.9% vs. 45.8%, p = 0.056) and were more likely to have been diagnosed before childbirth as well (39.8% vs. 24.2%, p < 0.001). Conclusions Women giving birth by CSMR more often suffer from psychiatric disorders both before and after delivery. This indicates that these women are a vulnerable group requiring special attention from obstetric- and general health-care providers. This vulnerability should be taken into account when deciding on mode of delivery.